The Star and the Scepter : A Diplomatic History of Israel - Navon, Emmanuel (Book collections on Project MUSE., 2020)
"The first all-encompassing book on Israel's foreign policy and the diplomatic history of the Jewish people, The Star and the Scepter retraces and explains the Jews' interactions with other nations from the ancient kingdoms of Israel to modernity"--